Pelaksanaan Pembelajaran Pendidikan Agama Islam Bagi Anak Berkebutuhan Khusus Tunagrahita di Masa Pandemi Covid-19 - Datul Ishmi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
This study aims to find out the implementation of PAI learning in two extraordinary schools, namely SLB Koto Agung and SLB Negeri 1 Pulau Punjung. This type of research is qualitative research, the source of research data is pai teachers in both SLB research places, and learners, data analysis techniques used are comparisons. The results showed that in SLB Koto Agung and SLB N 1 Pulau Punjung the implementation of learning using the 2013 curriculum, and the learning methods applied were methods.ceramah, demonstrasi,.tanya answer, drill, repetition, and assignment. There are similarities in the implementation of PAI learning in both SLB, namely the type of curriculum used, while the differences in general are in the implementation of learning during the pandemic, SLB Koto Agung does not do online learning but offline and does not visit, the assignment is by parents picking up questions to school, and within a week children do face-to-face to school, SLB Koto Agung gets good support from parents of students. Meanwhile, SLB N 1 Pulau Punjung in the implementation of PAI learning during the pandemic visited in turn, and the support from parents was less so providing support as well as in SLB Koto Agung.